2020
DOI: 10.3389/fimmu.2020.575816
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Effects of Aggregation-Induced Emission Materials

Abstract: Nanotechnology is widely used in the fields of biology and medicine. Some special nanoparticles with good biocompatibility, hydrophilicity, and photostability can be used as ideal systems for biomedical imaging in early diagnosis and treatment of diseases. Among them, aggregation-induced emission materials are new antiaggregation-caused quenching nano-imaging materials, which have advantages in biocompatibility, imaging contrast, and light stability. Meanwhile, heterogeneity of nanoparticles may cause various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In order to deliver IDO1 inhibitors to tumors more efficiently, a novel strategy to enhance the upload of epacadostat into tumor sites is required. Given their capacity for controlled and targeted drug release to specific cells, nanomaterials are critical in tumor therapy (42)(43)(44)(45). Lu et al (46)have revealed that INCB24360 delivery via a chlorin-based metal-organic framework achieved positive outcomes using combination photodynamic therapy and IDO1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to deliver IDO1 inhibitors to tumors more efficiently, a novel strategy to enhance the upload of epacadostat into tumor sites is required. Given their capacity for controlled and targeted drug release to specific cells, nanomaterials are critical in tumor therapy (42)(43)(44)(45). Lu et al (46)have revealed that INCB24360 delivery via a chlorin-based metal-organic framework achieved positive outcomes using combination photodynamic therapy and IDO1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In order to deliver IDO1 inhibitors to tumors more efficiently, a novel strategy to enhance the upload of epacadostat into tumor sites is required. Given their capacity for controlled and targeted drug release to specific cells, nanomaterials are critical in tumor therapy ( 42 45 ). Lu et al.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Moving forward to the biocompatibility evaluation of AIE-based materials, ADMET properties of solubilized AIE nanomaterials have been extensively investigated. [33] However, the majority of efforts have been devoted to improving the absorption of AIE-based nanomaterials for enhanced diagnostic and therapeutic efficiencies. [34] Imbalanced proteostasis often leads to proteome misfolding and aggregation and causes cellular proteome stress that is invisible to current cell viability and toxicity measurements.…”
Section: Introductionmentioning
confidence: 99%
“…26 In Wu's review, they focused on summarizing the immunobiological applications and solutions to potential risks associated with AIE materials, and summarized the latest developments, biological effects and biomedical applications of other nanoimaging materials to provide new ideas and approaches for diagnostic and therapeutic imaging with nanomaterials. 27 There is also a review by Tang et al that summarized recent results in the development of AIE probes for cancer therapeutics and discussed some key examples. 28 Conferring the AIE characteristics to conventional fluorescent probes can effectively solve the problems of conven-tional probes used in detecting enzymes.…”
Section: Introductionmentioning
confidence: 99%